Touching Philosophy, Sounding Religion, Placing Education. - Schroeder, Steven (Boston : BRILL, 2002)
This book redefines religious studies as a field in which a plurality of disciplines interact. A social science when understood as a body of knowledge, religion is also marked by discovery, appreciation, orientation, and application-an interplay of the arts and sciences. Teaching religious studies involves the question of the occupation of territories and disentangling occupation from violence.
SEVEN A Laboratory for Civil Discourse -- 1. Experiment -- 2. City Speech -- 3. The Classroom As City -- REFERENCES -- ABOUT THE AUTHOR -- INDEX -- Value Inquiry Book Series -- Titles Published
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Religion -- Philosophy; Religion -- Study and teaching; Religion -- Philosophie; Religion -- Étude et enseignement